Implementasi Pendidikan Islam Terpadu Di Sekolah Menengah Atas Islam Terpadu Putri Abu Hurairah Mataram Nusa Tenggara Barat Tahun 2015 - Syarifuddin, Syarifuddin, Dr. Abdullah Aly, M.Ag, Dr. Ari Anshori, M.Ag (2016)
ABSTRACT Reform of Islamic education is growing and dynamic. Oneof the Islamic educational institutions that are popular today are integrated Islamic school. Implementation of integrated Islamic education is an effort to increase student performance both cognitive, affective and psychomotor. Integrated Islamic school is a solution in providing character education. SMAIT daughter of Abu Hurairah Mataram is one of the schools that implement an integrated model of Islamic education. Implementation of integrated Islamic education in SMAIT daughter of Abu Hurairah Mataram expected to form an intelligent generation in science and technology and has a noble character and versatile preformance serve the community. The formulation of the problem in this research is twofold what are the components of the integration of Islamic education in SMAIT daughter of Abu Hurairah Mataram and How the implementation of integrated Islamic education in SMAIT daughter of Abu Hurairah Mataram in 2015. The aim of this study was to determine the alignment of the components of Islamic education in SMAIT Abu Hurairah Mataram daughter in 2015 and the implementation of an integrated Islamic education in SMAIT daughter of Abu Hurairah Mataram in 2015. the research is a field research with the research resources are SMAIT daughter of Abu Hurairah Mataram. This research method is descriptive qualitative research. Data collection techniques with documentation, interviews and observations. Data was analyzed using a comparative pattern. The results of this study describes the integration of the components of Islamic education in SMAIT daughter of Abu Hurairah Mataram which includes the integration of purpose, alignment of curriculum (teaching materials, curriculum organization, methods, domain, evaluation), the integration of education personnel and facilities and integration management. The implementation of integrated Islamic education in SMAIT daughter of Abu Hurairah Mataram 2015 includes three processes: (1) development of integrated Islamic education program tailored to hours of regular study hours and hours studying the boarding school. (2) the implementation of a unified Islamic learning by combining material from the government curriculum and curriculum boarding school. Evaluation of integrated Islamic education to carry out evaluations on cognitive, affective and psychomotor. Keywords: implementation; Islamic education; integrated Islamic education.